Literature Review: Konflik dan Manajemen Konflik Di Rumah Sakit - Mardiyanthi, Indah; Sjattar, Elly Lilianty; Irwan, Andi Masyitha (Jurnal Keperawatan Muhammadiyah, 2019)
ABSTRACTIntroduction: Conflict is a complex process that cannot be avoided. Demands that health workers can provide comprehensive services influence on increasing interaction between health workers. The purpose of this literature review is to obtain information about conflicts and their management in hospitals.Methods: Article searches were carried out in four database journals namely Google Scholar, ProQuest, Pubmed, and Wiley. The keywords used are "conflict management" OR "conflict management style" AND "nurse" AND "physician. Obtained 1911 articles which were then filtered out to select 11 articles relevant to the purpose.Results: A total of 11 articles were found discussing the causes of conflict such as individual, organizational and interpersonal factors. Avoiding is the main choice in managing conflict followed by collaboration. Demographic variables such as gender, age, level of education, emotional intelligence, personality, length of work and managerial position are variables that influence the use of strategy.Discussion: Conflict and its management are motivated by many factors, therefore it is important to assess appropriately the influencing factors so that they are expected to have an impact on the conflict management approach used by nurses and doctors.Â Keywords: conflict, conflict management, doctors, nurses.